Notes For a Discussion on Unequal Exchange and the Marxist Theory of Dependency - Féliz, Mariano (2021)
The debate on the decline of the terms of trade in dependent countries was never fully integrated into the Marxist theory of dependency. The attempt to articulate it through the category of unequal exchange was not particularly systematic. This paper seeks to recover those debates and will attempt to account for the relevant articulations in the light of a present revitalisation of studies in the field of Marxist dependency theory. To this end, we will recover the classical discussions around unequal exchange in order to discuss their points of contact with the Marxist theory of dependency and some contemporary debates around the transfer of value and the super-exploitation of labour and nature.
Keywords: Dependency; Unequal exchange; Marxism; Value-theory